Cryptochrome-Related Abiotic Stress Responses in Plants - D'Amico-Damiao, Victor [UNESP]; Carvalho, Rogerio Falleiros [UNESP] (Frontiers Media Sa, 2018)
It is well known that light is a crucial environmental factor that has a fundamental role in plant growth and development from seed germination to fruiting. For this process, plants contain versatile and multifaceted photoreceptor systems to sense variations in the light spectrum and to acclimate to a range of ambient conditions. Five main groups of photoreceptors have been found in higher plants, cryptochromes, phototropins, UVR8, zeitlupes, and phytochromes, but the last one red/far red wavelengths photoreceptor is the most characterized. Among the many responses modulated by phytochromes, these molecules play an important role in biotic and abiotic stress responses, which is one of the most active research topics in plant biology, especially their effect on agronomic traits. However, regarding the light spectrum, it is not surprising to consider that other photoreceptors are also part of the stress response modulated by light. In fact, it has become increasingly evident that cryptochromes, which mainly absorb in the blue light region, also act as key regulators of a range of plant stress responses, such as drought, salinity, heat, and high radiation. However, this information is rarely evidenced in photomorphogenetic studies. Therefore, the scope of the present review is to compile and discuss the evidence on the abiotic stress responses in plants that are modulated by cryptochromes.
Keywords: abiotic stress acclimation; blue-light photoreceptor; cryptochromes; drought; heat; high light; salinity